Resposta do algodoeiro submetido a lâminas de irrigação excessiva e deficitária com diferentes concentrações de água salina - Pereira, Jordânia Maria Gabriel (2017)
Limiting water as an input by quantity and quality is a problem for agricultural production: a possible solution and mitigation of the problem would be to save water by using deficit irrigation and / or salt water without damaging crop development. It is known that both deficit irrigation and saltwater use result in stresses that can affect several essential biochemical and physiological processes, since they compromise cellular functioning. However, the literature shows that the isolated and mainly combined effects of these stresses still lack studies, particularly on cotton cultivation. Thus, the objective of this work was to evaluate the effects of quantity (water excess or deficit) and quality (salt concentration) of irrigation water under growth, and cotton gas exchange. Three irrigation slides (70, 100 and 130% of field capacity) and four salinity levels (0.5, 2.5, 5.0, 7.5 ds m-1) were used as experimental strategy, with five Repetitions, totaling 60 experimental units, arranged in a factorial scheme (3 × 4) and completely randomized design. The plant material used was cotton cultivar Fiber max 910, sown in soil and humus (2: 1). The variables analyzed were soil electrical conductivity, growth (biomass allocation, plant height, stem diameter, number of leaves per plant and leaf area), water potential measurements and gas exchange. Plant biomass growth and biomass production was markedly reduced by water deficit and soil salinity conditions. The stresses influenced in an isolated manner the leaf emission, stem diameter, leaf area, specific leaf area, foliar weight ratio and biomass of beetles. The effects of the interaction between the stresses were felt in the dry biomass production of leaves, stem, flowers and total. Root biomass did not show changes in both stresses. The degree of water stress was able to accentuate the susceptibility to salinity and the plants are generally qualified as moderately tolerant to the effects of salinity and when associated with an excessive blade the cotton was classified as tolerant to all levels of salinity. Photosynthesis and transpiration were significantly influenced by the interaction of irrigation slides, salinity and evaluation periods. The gs was reduced by both isolated stresses. Thus, the water deficit as well as the salt stress had little effect on the cotton gas exchange, reducing the stomatal conductance slightly, which was not enough to reduce the rate of liquid photosynthesis.